2018
DOI: 10.1016/j.drugpo.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus in young people who inject drugs in four Colombian cities: A cross-sectional study using Respondent Driven Sampling

Abstract: Although prevalence of HCV in PWID in Colombia is lower than that reported for other countries, the described demographic characteristics and diverse risky injection behaviors on each city, in the context of a young PWID population with a short injection drug use history, should be taken into account in order to guide efforts towards preventing and reducing risk of HCV infection in PWID in Colombia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…was the main risk factor [16], and a cross-sectional study with 918 PID from four Colombian cities (Armenia, Bogotá, Cúcuta and Pereira) found a prevalence of 27.3% in HCV, and the risk factors were: had a history of injection drug use of 5 years or more, higher injection frequency, daily use of gifted, sold, or rented needles and being HIV seropositive [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…was the main risk factor [16], and a cross-sectional study with 918 PID from four Colombian cities (Armenia, Bogotá, Cúcuta and Pereira) found a prevalence of 27.3% in HCV, and the risk factors were: had a history of injection drug use of 5 years or more, higher injection frequency, daily use of gifted, sold, or rented needles and being HIV seropositive [17].…”
Section: Introductionmentioning
confidence: 99%
“…In indigenous populations of the Colombian Amazon the prevalence of HBV (using anti-HBc) was 3.6% (46/1275) in children and 30.9% (177/572) in mothers; genetic studies in the positives cases showed a predominance of subgenotypes F1b and F1a, with identification of two HBV escape mutants G145R and W156* in a child with occult HBV; mutations L109R and G130E of the HBsAg sequence were also identified [ 15 ]. Specifically in people who inject drugs (PID), a study about HIV/HCV which included 50 people from Pereira-Colombia shown that had sex with other key groups was the main risk factor [ 16 ], and a cross-sectional study with 918 PID from four Colombian cities (Armenia, Bogotá, Cúcuta and Pereira) found a prevalence of 27.3% in HCV, and the risk factors were: had a history of injection drug use of 5 years or more, higher injection frequency, daily use of gifted, sold, or rented needles and being HIV seropositive [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…La edad promedio de los participantes del estudio fue de 26,3 ± 6,5 años, y la frecuencia de infección por VHC fue de 28,8 % con un rango entre 7,6 % (Bogotá) y 47,4% (Pereira) según la ciudad. El riesgo de infección por VHC estuvo asociado al uso de drogas inyectables durante cinco años o más (OR = 3,1; IC95%: 1,3-7,2) ( 35 , 36 ). La coinfección de VHC y VIH en esta población fue de 3,2%, con un rango de 1% en Bogotá a 5,6% en Pereira ( 36 ).…”
Section: Resultsunclassified
“…En PID se han realizado varios estudios en diferentes regiones del país con un rango de seroprevalencia entre 7,6% y 47,4% (cuadro 1) (28,(33)(34)(35)(36). En un importante estudio realizado en 1 123 PID en cinco ciudades del país (Bogotá, Medellín y Cúcuta −en la frontera con Venezuela− y Pereira y Armenia en la región andina-eje cafetero) se describe la infección por VHC.…”
Section: Resultsunclassified
“…irrespective of the varied study designs and the very characteristics of RDS, especially the underlying network structures (e.g., Do et al, 2018;Liu et al, 2018;Toro-Tobón, Berbesi-Fernandez, Mateu-Gelabert, Segura-Cardona, & Montoya-Vélez, 2018). Conversely, others try to use some form of weighted logistic regression, adding weights obtained from reported network sizes (e.g., Hotton, Quinn, Schneider, & Voisin, 2018;Ndori-Mharadze et al, 2018;Szwarcwald et al, 2018).…”
mentioning
confidence: 99%